Remote Learning for Adults with Mild Cognitive Impairment in the New Landscape of COVID-19 Restrictions - TSIPTSIOS, Dimitrios (Advances in Social Sciences Research Journal, 2022)
Introduction: Mild Cognitive Impairment (MCI) is a transitional stage between the expected cognitive decline of normal aging and the more serious decline of dementia. Research interest focuses on the protection of this transition, through a combination of therapeutic interventions. Μaterials and Methods: 45 individuals with MCI who were followed up by the interdisciplinary team of our Memory School attended an online remote educational program that consisted of a series of cognitive and occupational therapy interventions designed to maintain their cognitive, executive, motor and emotional skills during the COVID-19 period. At baseline and at twelve-month follow-up all patients underwent several neuropsychological tests that included the Montreal Cognitive Assessment (MoCA), the Mini Mental State Examination (MMSE), the Functional Cognitive Assessment Scale (FUCAS), the Geriatric Depression Scale (GDS) and the Functional Rating Scale of Symptoms of Dementia (FRRSD). Also, the Barthel Index scale and the Timed Up and Go (TUG) test were utilized to assess functionality and mobility, respectively. Results: Within twelve months participants’ performance did not change significantly (MoCA; p=0.908, MMSE; p=0.625, FUCAS; p=0.782; GDS; p=0.218, FRSSD; p=0.18, Barthel Index; p=0.317, TUG; p=0.68). Results confirmed the hypothesis that cognitive, executive, motor and behavioral skills can be maintained through an online educational protocol during the COVID-19 lockdown period. Conclusions: It is proposed that similar educational protocols should be included in the design of strategic directions in the field of healthcare in MCI and dementia, especially in health crisis situations.